Antimicrobial resistance prevalence in commensal Escherichia coli from broilers, fattening turkeys, fattening pigs and veal calves in European countries and association with antimicrobial usage at country level. Issue 4 (18th March 2020) - Ceccarelli, Daniela; Hesp, Ayla; van der Goot, Jeanet; Joosten, Philip; Sarrazin, Steven; Wagenaar, Jaap A.; Dewulf, Jeroen; Mevius, Dik J.; EFFORT consortium, on behalf of the
Abstract : The aim of this article is to report on antimicrobial resistance (AMR) in commensal Escherichia coli from livestock from several European countries. The relationships with antimicrobial usage (AMU) at country level and harmonized indicators to cover the most relevant AMR aspects for human health in animal production were also investigated. E. coli were isolated in faeces from broilers and fattening pigs (from nine countries), and fattening turkeys and veal calves (from three countries) and screened against a fixed antimicrobial panel. AMU data were collected at farm and average treatment incidences stratified by antimicrobial class, country and livestock species were calculated. Associations between AMR and AMU at country level were analysed. Independent of animal species, the highest resistance was observed for ampicillin, sulphamethoxazole, tetracycline and trimethoprim. E. coli from broilers showed the highest resistance level for (fluoro)quinolones, and multidrug resistance peaked in broilers and fattening turkeys. Colistin resistance was observed at very low levels with the exception of fattening turkeys. High resistance to third- and fourth-generation cephalosporins was detected in broilers and fattening turkeys. The lowest levels of resistance were for meropenem, azithromycin and tigecycline (<1 %). Significant correlations between resistance and usage at country level were detected in broilers for polymyxins and aminoglycosides, and in fattening pigs for cephalosporins, amphenicols, fluoroquinolones and polymyxins. None of the correlations observed between AMR and AMU were statistically significant for fattening turkey and veal calves. The strength of the analysis performed here is the correlation of aggregated data from the same farms at country level for both AMU and AMR within antimicrobial classes.